Lecture 2: Discrete-Time Systems and Z-Transform
Lecture 2: Discrete-Time Systems and Z-Transform
Lecture 2: Discrete-Time Systems and Z-Transform
z-Transform
• z-Transform
• Inverse z-Transform
Continuous-Time Signals
• A signal that changes continuously in time:
e(t), −∞ < t < ∞, or t ≥ 0
1
Discrete-Time Signals
• A signal (sequence, or series) whose
values are defined only at discrete times:
e(k), k = · · · , −1, 0, 1, · · · or k = 0, 1, 2, · · ·
2
Digital Signals
y(t)
continuous-time
signal
ŷ(kT ) y(kT )
c(kT )
D/A Computer Quantizer
discrete-time
signal
digital signal
3
Transfer Functions of Continuous-Time
LTI Systems
• Taking Laplace transform (assuming zero initial conditions):
Y (s) βn sn +···+β1 s+β0
H(s) = E(s)
= αn sn +···+α1 s+1
4
Example of Discrete-Time LTI Systems
Example 1: Population of A Species (Fibonacci)
y(k): population of the k-th generation, with y(0)=1
Assumptions:
(i) each individual starts duplicating itself after two generations
(ii) no death from aging, and no migration
5
Euler’s Methods
First order derivative
Euler Forward Approximation:
6
z-Transform
• Given a discrete-time signal
f (k), k = · · · , −1, 0, 1, · · · or k = 0, 1, 2, · · ·
Its (double-sided) z-transform is defined by
∞
F (z) = Z[f (k)] = k=−∞ f (k)z −k , k = · · · , −1, 0, 1, · · ·
δ(k − n)
(n is an integer)
7
More General Discrete-Time Signals
Discrete-time unit step function
u(k) = 1, k = 0, 1, 2, · · ·
z
U(z) = z−1 DOC: |z −1 | < 1
More generally
f(k) = rk , k = 0, 1, 2, · · ·
F (z) = DOC:
Properties of z-Transform
Linearity: (α,β∈ℜ)
(shift right)
(shift left)
Example: f (k) = rk , n = 1
8
Properties of z-Transform
Initial Value Theorem:
f (0) = limz→∞ F (z)
Final Value Theorem:
f (∞) = limk→∞ f(k) = limz→1 (z − 1)F (z) (if exists)
Example:
f (k) = u(k) f (k) = r k
Properties of z-Transform
k
Convolution: let f1 (k) ∗ f2 (k) = l=0 f1 (l)f2 (k − l) be the convolution of
the two discrete-time signals. Then
Z[f1 (k) ∗ f2 (k)] = F1 (z)F2 (z)
Example:
dF (z)
Another property: Z[k f (k)] = −z dz
rz
Example: Z[kr k ] = (z−r)2
A list of the properties of z-transform can be found in Table 2-2, pp. 37.
9
Inverse z-Transform
• Given the z-transform F(z), how do we find the sequence
f (k), k = 0, 1, 2, · · ·
so that F(z) is the z-transform of f(k):
∞ −k
F (z) = k=0 f (k)z .
Drawbacks: good by hand or computer for a few f(k), no idea about general f(k)
10
Inversion Formula Method
The inverse z-transform of F(z) is given by
f(k) = [residue of F (z)z k−1 ]z=p
where the summation is over all the poles p of F(z)zk-1
residue at a simple pole z=a:
(residue)z=a = (z − a)F (z)z k−1 z=a
residue at a pole z=a of multiplicity m:
1 dm−1
(residue)z=a = (m−1)! dz m−1 (z − a)m F (z)z k−1 z=a
z
Example: F (z) = z 2 −3z+2
Example: 1
F (z) = z(z−1)
11
Partial Fraction Expansion Method
z
• If F (z) = z−p , then from previous result
f (k) = Z −1 [F (z)] = pk , k = 0, 1, 2, . . ..
pz
• If F (z) = (z−p)2 , then
f (k) = Z −1 [F (z)] = kpk , k = 0, 1, 2, . . ..
• ….
Simple Case
Assume that the denominator of F(z) can be factorized as
bm z m +···+b1 z+b0
F (z) = (z−p1 )···(z−pn )
and the poles p1,…,pn are all distinctive and nonzero. Then
F (z) c0 c1 c2 cn
z = z + z−p1 + z−p2 + ··· + z−pn
where the constants are residues given by
c0 = F (z)z=0 ci = (z − pi ) F z(z) z=pi
As a result,
12
Example
1
F (z) = z2 −3z+2
13
Exercise
1
F (z) = z(z−1) Z −1 [F (z)] =?
Alternative method: find the inverse of z2F(z) first, then shift to the right by two steps
For general complex poles case, read the textbook pp. 44-45.
14
Solution of Linear Difference Equations
Solution by Iterations
• The most obvious approach is by iterations
– Easily implemented by computers
f or k=0:N
y(k) = · · ·
..
.
end
15
Zero-State Response by z-Transform
• Assuming zero initial conditions:
y(−1) = y(−2) = . . . = y(−n) = 0
and e(−1) = e(−2) = . . . = e(−n) = 0
• Taking the z-transform of the equation
y(k) = bn e(k) + bn−1 e(k − 1) + · · · + b0 e(k − n)
−an−1 y(k − 1) − · · · − a0 y(k − n)
we have
16
Zero-Input Response by z-Transform
Find the output (called zero-input response) of the system
Idea: instead of dealing with double-sided signal y(k) and e(k), we define
ŷ(k) = y(k − 1), ê(k) = e(k − 1)
17
Full Response
• Superposition Law: For an LTI system, the response
under non-zero input and non-zero initial condition is the
sum of the zero-state and zero-input responses
18